Influência da tributação sobre o desempenho das cooperativas de crédito singulares brasileiras - Rosemary da Paixão Oliveira (2023)
ABSTRACT The objective of this research was to verify the influence of taxation on the performance of Brazilian singular credit cooperatives from 2014 to 2021. Based on theoretical foundations from various studies in the literature on the subject of taxes, the study also includes an analysis of the macroeconomic effects of the COVID-19 health crisis on the performance of Brazilian credit cooperatives. This is due to changes in the legislation of the national financial system that affected the rates of the Social Contribution on Net Profit (CSLL), increasing the rate during the pandemic period. Using the data from the semi-annual database of BACEN (Brazilian Central Bank) regarding singular credit cooperatives from 2014 to 2021, the study employs the econometric approach of dynamic panel data using the Generalized Method of Moments (GMM). The research highlights that Brazilian credit cooperatives use tax management through Base Erosion and Profit Shifting (BEPS) in order to achieve better financial performance indicators, and that recessive periods can undermine the performance of credit cooperatives. The management of institutions is affected by the tax burden, including credit unions. In Brazil, credit cooperatives are important to mitigate social inequality and restricted access to credit. The research analyzed the influence of taxation on Brazilian individual credit unions and observed differences in the values of tax planning proxies during economic crises. The effective tax rate was also analyzed, showing a drop during the 2015 economic crisis and an increase during the COVID-19 crisis. The study concluded that the tax environment affects the performance of credit unions in different market segments. Brazilian credit unions adopt tax management practices to improve their financial performance. Higher levels of management are observed in credit unions classified as "equity and loan", while those classified as "classic" have lower management. The size of cooperatives, net worth and gross revenue also influence financial performance. The diversification of services and tariffs also contributes to better performance. However, recessive periods can negatively affect the performance of these cooperatives. Future studies are needed to develop specific tax management proxies for different groups of credit unions.